TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI BARANG MYSTERI BOX DI MARKET PLACE SHOPEE - Pasha, Indra Nugraha; Asyiqin, Hisyam (Collegium Studiosum Journal, 2024)
The mystery box business involves buying and selling online. The items sold in mystery box products vary. In general, this purchase implies a surprising thought, so that the buyer in particular is not aware of the contents of the mystery box, but can only determine the type of product. Shopee is a platform that sells mystery box products and is currently popular among the public. Different from ordinary buying and selling, this buying and selling arouses the interest of buyers because this business is considered truly unique and profitable, but many buyers still regret it and feel they have been disadvantaged. This is because the seller does not declare the goods inside and therefore the goods received cannot be returned. In this research, the problem formulation is how the concept and practice of mystery box buying and selling transactions sold on Shopee and how mystery box buying and selling transactions on Shopee are reviewed from Islamic law. The author uses descriptive analysis research methods with actions based on quality. Data was collected through literature study. The research results show that the law of buying and selling mystery boxes is haram, because the buying and selling of mystery boxes on Shopee is effectively canceled based on the terms of the Ba'i Salam Agreement because one of the Ba'i Salam conditions, namely the privileges and types of goods, are not met. And such transactions are also included in buying and selling gharar.